Analisis Kebijakan Pemotongan PPH 23 atas Pengembalian Premi Reasuransi/Komisi Reasuransi - Inawati, Inawati (Syntax Corporation, 2025)
Reinsurance companies (reasuradur) carry out risk coverage cooperation with insurance companies (asuradur) by receiving some amount of premium payments (reinsurance premium) from insurance companies (asuradur). Meanwhile, the insurance company will receive a reinsurance commission/ceding commission in the form of a refund premium as an implication of cooperation in the management of risk coverage and joint costs. in the view of insurance companies, the return of ceding premiums/commissions received by the insurer is a